2013
DOI: 10.1371/journal.pone.0082605
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Ubiquitous Pelagic Diatom Thalassiosira weissflogii to Darkness and Anoxia

Abstract: Thalassiosira weissflogii, an abundant, nitrate-storing, bloom-forming diatom in the world’s oceans, can use its intracellular nitrate pool for dissimilatory nitrate reduction to ammonium (DNRA) after sudden shifts to darkness and anoxia, most likely as a survival mechanism. T. weissflogii cells that stored 4 mM 15N-nitrate consumed 1.15 (±0.25) fmol NO3 - cell-1 h-1 and simultaneously produced 1.57 (±0.21) fmol 15NH4 + cell-1 h-1 during the first 2 hours of dark/anoxic conditions. Ammonium produced from intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 69 publications
3
54
1
1
Order By: Relevance
“…We also note that future research is needed in terms of understanding the resistance of proteinaceous sediment material to acid hydrolysis. To answer this question, it will be particularly important to quantify proteinaceous vs. non-proteinaceous fractions of organic nitrogen in the sediment (Keil et al, 2000). The single study to date that directly compares stable isotope values of bulk sedimentary nitrogen vs. the hydrolyzable proteinaceous amino acid pool suggests that the non-proteinaceous fraction of organic nitrogen is substantial (Batista et al, 2014).…”
Section: Sedimentary δ 13 C Aa Patternsmentioning
confidence: 99%
“…We also note that future research is needed in terms of understanding the resistance of proteinaceous sediment material to acid hydrolysis. To answer this question, it will be particularly important to quantify proteinaceous vs. non-proteinaceous fractions of organic nitrogen in the sediment (Keil et al, 2000). The single study to date that directly compares stable isotope values of bulk sedimentary nitrogen vs. the hydrolyzable proteinaceous amino acid pool suggests that the non-proteinaceous fraction of organic nitrogen is substantial (Batista et al, 2014).…”
Section: Sedimentary δ 13 C Aa Patternsmentioning
confidence: 99%
“…To calculate the intracellular NO3 concentration, 25 μL of the well-mixed pellet was diluted 1:10 in NaCl solution (salinity 30) plus 4% formaldehyde for diatom cell counting in a Fuchs-Rosenthal counting chamber. The remaining pellet and 100 μL of the cell-free supernatant were separately frozen at -20°C for (intracellular) NO3 analyses with an NO x analyser (CLD 66s, EcoPhysics; for details see Kamp et al, 2011, 2013). The remaining cell-free supernatant was frozen at -20°C for measurement of NH4+, 15 NH4+, and 15 NO2 concentrations (for details see Kamp et al, 2013; Stief et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The vertical transport of intracellularly stored NO3 within sinking diatom-bacteria aggregates (Stief et al, 2016) has so far not been documented in situ . To date, diatoms are the only known NO3-storing microorganisms in marine snow, e.g., the pelagic species Skeletonema marinoi and Thalassiosira weissflogii (Kamp et al, 2011, 2013; Stief et al, 2016). Both genera are very abundant in the ocean and can contribute significantly to spring blooms and subsequent aggregate formation (Bresnan et al, 2009; Degerlund and Eilertsen, 2010; Leblanc et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can aid survival from months to decades in dark, anoxic conditions. In a later report, Kamp et al ( 2013 ), showed that a possible survival mechanism used by the abundant oceanic species Thalassiosira weissfl ogii was the ability to use its intracellular nitrate pool for dissimilatory nitrate reduction to ammonium after sudden shifts to darkness and anoxia. Also, in stable oligotrophic conditions, such as subtropical regions and the surface layers of stratifi ed temperate pelagic regions in summer, some diatoms have developed more adaptable approaches, including symbiosis with nitrogen-fi xing cyanobacteria ( Fig.…”
Section: Resting Stagesmentioning
confidence: 99%